PENGARUH CELEBRITY ENDORSE, GAYA HIDUP, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA BRAND ELZATTA HIJAB (Studi Kasus Pada Mahasiswa Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Malang Angkatan 2016-2018) - Mar’atus Sa’diyah; N. Rachma; Siti Asiyah (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis research was conducted to determine the effect of Celebrity Endorse, Lifestyle and Brand Image on Purchasing Decisions on the Elzatta Hijab Brand. This research was conducted at the Faculty of Economics and Business, Islamic University of Malang, located at Jl. MT. Haryono No.193 Malang. This type of research data in the form of quantitative data, i.e. the data can be obtained through interviews, observations, discussions or observations (surveys). This research is a research that uses correlational research, and the source of the data used is primary data by distributing Likert scale cieoner to students at the Faculty of Economics and Business, Islamic University of Malang. The sample calculation in this study uses the Maholtra formula which produces 100 respondents. The results of this study are the variables Celebrity Endorse, Lifestyle and Brand Image influence simultaneously or partially on Purchasing Decisions. Keywords: celebrity endorse, lifestyle, brand image and purchasing decisions